TEST OF A SYMMETRICAL 4-DETECTOR COMPTON POLARIMETER USING LOW-TEMPERATURE NUCLEAR ORIENTATION - Deng, J; Hamilton, J; Ramayya, A; Rikovska, J; Stone, N; Croft, W; Piercey, R; Morgan, J; Mantica, P (Kluwer Academic Publishers, 1992)
A symmetrical four-detector Compton polarimeter was used to measure the linear polarization of gamma-rays emitted from nuclei oriented by the hyperfine interaction at low temperature. Its polarization detection efficiency was determined in the range 0.3-1.4 MeV and compared with some other polarimeters. © 1992 J.C. Baltzer A.G., Scientific Publishing Company.